Kaposi’s sarcoma-associated herpesvirus glycoprotein K8.1 is critical for infection in a cell-specific manner and functions at the attachment step on keratinocytes - Liu, Shanchuan; Großkopf, Anna K.; Yang, Xiaoliang; Mannheim, Maximilian E.; Backovic, Marija; Scribano, Stefano; Schlagowski, Sarah; Enßer, Armin; Hahn, Alexander S. (Journal of Virology, 2023)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is associated with Kaposi’s sarcoma and B cell malignancies. K8.1, the major antigenic component of the KSHV virion, has been reported to play a critical role in the infection of B cells, but otherwise its function remains enigmatic. We created a K8.1 knockout virus (KSHVΔK8.1) in the BAC16 genetic background and analyzed its infectivity on a range of adherent cells. We observed a strong defect on several epithelial cells, such as the HaCaT keratinocyte cell line, human embryonic kidney (HEK) 293T, and A549 lung epithelial cells. However, we did not observe such a defect in other cells, including lymphatic and blood endothelial cells. Mechanistically, we found that reduced infectivity of the K8.1 knockout virus correlated with reduced attachment to HaCaT cells. The defect in infectivity of KSHVΔK8.1 could be rescued by complementation through expression of K8.1 in KSHVΔK8.1 producing cells by means of a lentiviral vector. In a coculture infection model with iSLK producer cells, KSHVΔK8.1 was highly efficient at infecting the BJAB B cell line but was significantly impaired at infecting the MC116 B cell line, in line with a previous report. In fusion assays together with the gH/gL glycoprotein complex and gB, the components of the conserved herpesviral core fusion machinery, we did not observe activation of membrane fusion by K8.1 or its R8.1 homolog of the rhesus monkey rhadinovirus. In summary, we found K8.1 to function in a highly cell-specific manner during KSHV entry at the attachment step, playing an important role in the infection of epithelial cells. IMPORTANCE Kaposi’s sarcoma-associated herpesvirus (KSHV) is the causative agent of several B cell malignancies and Kaposi’s sarcoma. We analyzed the function of K8.1, the major antigenic component of the KSHV virion in the infection of different cells. To do this, we deleted K8.1 from the viral genome. It was found that K8.1 is critical for the infection of certain epithelial cells, e.g., a skin model cell line but not for infection of many other cells. K8.1 was found to mediate attachment of the virus to cells where it plays a role in infection. In contrast, we did not find K8.1 or a related protein from a closely related monkey virus to activate fusion of the viral and cellular membranes, at least not under the conditions tested. These findings suggest that K8.1 functions in a highly cell-specific manner during KSHV entry, playing a crucial role in the attachment of KSHV to, e.g., skin epithelial cells.
CRIS-Team Scopus Importer:2023-11-17
Keywords: attachment; entry; glycoproteins; Kaposi's sarcoma; Kaposi's sarcoma-associated herpesvirus; KSHV; virus